The Influence of Insecurity, Perceived of Technology Innovativeness, Perceived Ease of Use and Perceived Usefulness on Consumers Intention to Use Electronic Toll Payment Cards - Sudirjo, Frans; Tawil, Muhamad Risal; Imanirubiarko, Sabda; Judijanto, Loso; Fauzan, Tribowo Rachmat (SEULANGA SYSTEM PUBLISHER, 2023)
The purpose of this study is to examine how optimism, innovativeness, and insecurity affect perceptions of usefulness and ease of use, as well as how these perceptions affect behavioral intention to use. A descriptive research design was employed in this study. The participants in this study are Jakartan e-toll card customers. With a sample size of 100 respondents, this study combined the judgmental sampling technique with a non-probability sampling method. Questionnaires were randomly distributed using a non-probability sampling technique in order to obtain data. Based on the data processing and analysis outcomes, the following conclusions may be drawn from this study: Because optimism has a positive standard coefficient, it positively affects perceived ease of use. Because innovativeness has a positive standard coefficient, it positively affects perceived ease of use. Because insecurity has a positive standard coefficient, it positively affects how easy something is considered to be. Because perceived ease of use has a positive standard coefficient, it positively affects perceived usefulness. Because perceived ease of use has a standard coefficient of positive value, it positively influences behavioral intention.